Raman Spectroscopy and Surface Enhanced Raman Scattering (SERS) for the Analysis of Blue and Black Writing Inks: Identification of Dye Content and Degradation Processes - Saviello, Daniela; Trabace, Maddalena; Alyami, Abeer; Mirabile, Antonio; Baglioni, Piero; Giorgi, Rodorico; Iacopino, Daniela (Frontiers in Chemistry, 2019)
Raman spectroscopy and Surface Enhanced Raman Scattering (SERS) were applied to the analysis of blue and black writing inks. SERS was performed by application of plasmonic nanopastes constituted by Ag nanoparticles and Au nanorods directly on inks deposited on paper substrates under laser irradiation of 514 nm. It was found that SERS spectra were largely enhanced compared to Raman spectra and that Ag nanopastes produced much larger enhancements than Au nanopastes, due to a combination of plasmonic resonance, charge transfer and molecular resonance effects. All analyzed writing inks resulted constituted by Crystal Violet and other tryarylmethane dye mixtures, to which sometimes phthalocyanine dyes were also added (for example in Bic pens). SERS was also used for the identification of degradation processes occurring in artificially aged blue pens deposited on paper substrates. It was found that color alteration changed from ink to ink and varied from darkening to discoloration to slight fading, depending on the initial chemical composition. For inks containing Crystal Violet, two mechanisms associated to de-methylation and photo-reduction of excited dye to colorless leuco forms were identified.